Integrative reviews in Brazilian nursing postgraduation programs: a bibliometric study - Tábata Cerqueira Nascimento Nobre; Darci de Oliveira Santa Rosa; Ednalva Alves Heliodoro
ABSTRACT Objectives: to analyze the Brazilian scientific integrative review production in postgraduation nursing programs. Methods: bibliometric design, carried out in the database of dissertations and theses of the Coordination for the Improvement of Higher Education Personnel, in October 2018. Results: 35 dissertations and 1 thesis were found. Most studies were carried out at the University of São Paulo; the main methodological reference was Mendes, Silveira and Galvão (2008); for data collection, it was Ursi (2005). The most used database was CINAHL, followed by LILACS and PubMed. The period of publication varied from 5 to 30 years; and the sample, from 6 to 299 texts. Some studies did not mention keywords, data collection period, exclusion criteria or publishing period. Conclusions: despite the growing popularity of integrative review studies, they are undervalued in the stricto sensu postgraduation program in nursing and there are shortcomings in the implementation of the method, related to the absence of important elements.